Impact of COVID-19 on mucormycosis presentation and laboratory values: A comparative analysis - Sepideh Hejazi; Ali Gholampour Kargar; Sahar Ravanshad; Arash Ziaee; Maryam Emadzadeh; Mona Kabiri; Reza Khoshbakht; Mohammad Hossein Ahmadi; Masoumeh Hosseinpoor; Hamed Khosravi; Imtiaz Ahmed; Mehdi Bakhshaee (PLoS ONE, 2025)
Background The COVID-19 pandemic has led to an alarming increase in mucormycosis coinfections and its rapid progression. The overlapping risk factors and symptoms between COVID-19 and mucormycosis further complicate prompt detection, which is crucial for patient survival. This study aims to investigate potential differences in mucormycosis progression, initial symptom presentation, and laboratory value alterations in mucormycosis patients with COVID-19 history to enhance diagnostic accuracy and improve outcomes in this complex clinical scenario. Methodology This retrospective cohort study, conducted from April 1, 2021, to March 31, 2022, examined 102 patients diagnosed with mucormycosis at two primary teaching hospitals. Patients were categorized into two groups based on COVID-19 history. Variables included demographic information, clinical parameters, laboratory results, and outcomes. The study compared patient laboratory studies and presentation symptoms between COVID-19 history-positive and COVID-19 history-negative groups, with a particular focus on mortality rates and associated comorbidities such as diabetes, cancer and immunosuppressive treatment. Results Initial clinical presentations differed significantly, eneralized Estimating Equations (GEE) analysis, adjusted for comorbidities, revealed COVID-19 history was associated with increased platelet counts (P = 0.0311) and decreased facial swelling (P = 0.049) and fever symptom reporting (P < 0.001). Cancer history, diabetes, and immunosuppressive treatment also showed significant associations with various clinical and laboratory parameters. Laboratory analysis revealed significant differences between mucormycosis patients with and without COVID-19 history. The COVID-19 history-positive group showed lower WBC counts (P = 0.002), and higher hemoglobin levels (P < 0.001) compared to controls. Diabetes was more prevalent in COVID-19 history-positive patients, while cancer history was more common in controls. Conclusion This study reveals intricate relationships between COVID-19 history, mucormycosis, patient presentation, challenging earlier findings. Mucormycosis patients with COVID-19 history exhibited higher platelet counts and altered symptom presentation. The research highlights varied symptom patterns across patient subgroups and underscores the complexity of interactions between COVID-19, cancer, and diabetes in mucormycosis cases. These findings advocate multivariate analytical approaches to better understand these multifaceted relationships.